Peran Tadika (Taman Didikan Kanak-Kanak) dalam Mempertahankan Nilai-Nilai Keislaman dan Identitas Melayu di Pattani Thailand Selatan - Situmeang, Marini Kristina; Shiddiq Zikir, Alfaiq; Ullyawati; Mustaqilah, Syafirrah (Jurnal Riset dan Pengabdian Masyarakat, 2024)
The research aims to see the role of Tadika in maintaining the next generation based on Islamic values and Malay Pattani identity. The research method used in this paper is (field research) or field research. Field research is a method that involves collecting data directly from the location that is the focus of the research. In the context of this paper, field research was conducted in Lubuk Luas Village, Pattani, Southern Thailand, to obtain information about the role of Tadika in maintaining Islamic values and Malay identity. The results of this study indicate that Tadika has an important role in maintaining Islamic values, as well as playing an important role in shaping Malay personality as the next generation of identity. Tauhid, Fiqh, Morals and other teachings of Islamic values. And Tadika has a very important role in shaping the personality of Patani Malays.